Experimentação e educação ambiental: contribuições metodológicas - Montebello, Patricia Rosada [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
During the last centuries, the human being have been considered the center of the universe. The man believed that nature was at his disposal. Appropriated their processes, their cycles changed, redefined their spaces. Today, when faced with an environmental crisis which threatens the planet life, including the human life, the Science Education can contribute to a reconstruction of man-nature relationship in other terms. The transformation of teaching practices in the school environment, to be reflective, it is still a process that challenges the vast majority of teachers. As has been indicated by Guerra (2004), among others, the traditional teaching of content delivery is still very strong and certainly more deeply embedded in ideas and activities of the teachers who focus on environmental education. With it, a theory and pedagogical discourses in critical-reflexive actions is still a major obstacle. Therefore, new proposals for education and continuing education activities need to be formulated and presented based on the characteristics and needs breathing. Therefore propose changes in the way of teaching, where there is more room for a theory and praxis alone or with a only scientific truth. The scenery of society requires that knowledge is constructed to interconnect all disciplines, joining theory and practice so we can understand the whole and their relations in an integrated manner. It was proposed here a way to build a school and applying theoretical and practical activities involving experimental and seeking to meet the principles of Environmental Education for the training of citizens aware and critical. At the same time cares to use textbooks very rich in its pedagogical character that are present in schools and often are, forgotten and unused by teachers. From this way, I chose to Experimentoteca, ...(Complete abstract click electronic access below)

Durante os últimos séculos, o ser humano tem se considerado o centro do Universo. O homem acreditou que a natureza estava à sua disposição. Apropriou-se de seus processos, alterou seus ciclos, redefiniu seus espaços. Hoje, quando se depara com uma crise ambiental que coloca em risco a vida do planeta, inclusive a humana, o ensino de ciências naturais pode contribuir para uma reconstrução da relação homem-natureza em outros termos. A transformação das práticas pedagógicas no ambiente escolar, no sentido de serem reflexivas, é ainda um processo que desafia a grande maioria dos professores. Como já foi apontado por Guerra (2004), entre outros autores, o modelo tradicional de ensino de transmissão de conteúdos ainda é muito forte e certamente mais profundamente inserido no ideário e nas atividades pedagógicas dos professores que se debruçam sobre a educação ambiental. Com isso, transformar a teoria e os discursos em ações pedagógicas crítico-reflexivas ainda é um grande obstáculo. Portanto, novas propostas para o ensino e para ações de formação continuada precisam ser formuladas e apresentadas a partir das características e necessidades existentes. Assim se propõem mudanças na forma de se ensinar, onde não há mais espaço para uma práxis unicamente teórica e nem com uma única verdade científica. O atual panorama da sociedade exige que o conhecimento seja construído de modo a se interligar todas as disciplinas, unindo-se teoria e prática para que possamos compreender o todo e suas relações de forma integrada. Propôs-se aqui um modo de construir e aplicar uma aula teórico-prática, envolvendo atividades experimentais e buscando atender os princípios da Educação Ambiental, visando a formação de cidadãos conscientes e críticos. Ao mesmo tempo em que se preocupa ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Educação ambiental; Ciência – Experiência; Ciências (Primeiro grau) – Estudo e ensino; Proteção ambiental